2007
DOI: 10.1152/japplphysiol.01092.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pressure-induced deep tissue injury using intermittent electrical stimulation

Abstract: Pressure ulcers develop due to morphological and biochemical changes triggered by the combined effects of mechanical deformation, ischemia, and reperfusion that occur during extended periods of immobility. The goal of this study was to test the effectiveness of a novel electrical stimulation technique in the prevention of deep tissue injury (DTI). We propose that contractions elicited by intermittent electrical stimulation (IES) in muscles subjected to constant pressure would induce periodic relief in internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 48 publications
4
39
0
Order By: Relevance
“…Muscle contractions induced by electrical stimulation (ES) might help prevent PUs as they improve both the intrinsic risk factors for developing PUs, because ES may reduce atrophy, 5 improve blood flow and oxygenation, 6,7 and sitting pressure distribution as it redistributes pressure away from the IT area. 8 Levine et al [6][7][8] found that surface ES of the gluteal (g) muscles produces a sizeable pressure reduction below the ITs.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle contractions induced by electrical stimulation (ES) might help prevent PUs as they improve both the intrinsic risk factors for developing PUs, because ES may reduce atrophy, 5 improve blood flow and oxygenation, 6,7 and sitting pressure distribution as it redistributes pressure away from the IT area. 8 Levine et al [6][7][8] found that surface ES of the gluteal (g) muscles produces a sizeable pressure reduction below the ITs.…”
Section: Introductionmentioning
confidence: 99%
“…53 In this approach, electrical stimulation is applied for a short duration (on the order of seconds) with several minutes of recovery between stimulations. The muscle contractions produced by the intermittent bursts of stimulation mimic the natural repositioning movements subconsciously performed by able-bodied individuals in response to discomfort while sitting.…”
Section: Introductionmentioning
confidence: 99%
“…Solis et al found that superficial ES delivered every 10 min is sufficient to greatly reduce the extent of damage in the deep tissue exposed to constant external pressure. 19,20 When the external load decreases, the internal load decreases as well, but more insight into the relationship between IT pressure and deep tissue injury is needed to provide information on the validity of external interface pressure measurements.…”
Section: Discussionmentioning
confidence: 99%